2019
DOI: 10.1111/jne.12671
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and pathophysiological roles of hypothalamic astrocytes in metabolism

Abstract: The role of glial cells, including astrocytes, in metabolic control has received increasing attention in recent years. Although the original interest in these macroglial cells was a result of astrogliosis being observed in the hypothalamus of diet‐induced obese subjects, studies have also focused on how they participate in the physiological control of appetite and energy expenditure. Astrocytes express receptors for numerous hormones, growth factors and neuropeptides. Some functions of astrocytes include trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 140 publications
1
11
0
1
Order By: Relevance
“…30 At the cellular level, leptin enhances glucose uptake through GLUT1. 31,32 In this study, a reduction in plasma leptin levels was observed. The reduction in leptin levels may have inhibited glucose uptake into cells and increased glycogenolysis.…”
Section: Discussionsupporting
confidence: 59%
“…30 At the cellular level, leptin enhances glucose uptake through GLUT1. 31,32 In this study, a reduction in plasma leptin levels was observed. The reduction in leptin levels may have inhibited glucose uptake into cells and increased glycogenolysis.…”
Section: Discussionsupporting
confidence: 59%
“…The copyright holder for this preprint this version posted January 31, 2021. ; https://doi.org/10.1101/2021.01.29.428244 doi: bioRxiv preprint balance (57)(58)(59)(60), and a detailed analysis of brainstem and hypothalamus will be essential in determining causes for failure to thrive and lethality in the model. Gfap-targeted ASO treatment leads to long lasting suppression of GFAP transcript and protein to below wild-type levels in both mouse and rat models of AxD.…”
Section: Discussionmentioning
confidence: 99%
“…Intractable vomiting is also observed in neuromyelitis optica (NMO) spectrum disorders, where the autoimmune response against the high levels of APQ4 in circumventricular organs can lead to area postrema syndrome (56), suggesting astrocyte dysfunction may be a common denominator for frequent emesis in both AxD and NMO. Several studies have also tied astrocyte function to hypothalamic regulation of food intake and energy balance (57)(58)(59)(60), and a detailed analysis of brainstem and hypothalamus will be essential in determining causes for failure to thrive and lethality in the model. Gfap-targeted ASO treatment leads to long lasting suppression of GFAP transcript and protein to below wild-type levels in both mouse and rat models of AxD.…”
Section: Gfap Suppression Rescues Motor Deficits and Axd Phenotypesmentioning
confidence: 99%
“…Therefore, astrocyte–neuron communication is key in the regulation of energetic signal transport and sensing by neurons. Indeed, studies have described the role of astrocytes in the detection of leptin, glucose, fatty acids, and amino acids and their involvement in the metabolic balance [ 218 , 219 , 220 , 221 , 222 , 223 ]. The role of astrocytes in glutamate recycling is also associated with the lactate supply to neurons for neurotransmitter action [ 222 ].…”
Section: Glycemic Index and Brain Regulation Of Energy Homeostasismentioning
confidence: 99%